Manajemen Risiko Pada Penerbitan Sukuk Usaha Kecil Menengah (UMKM): Perspektif Kaidah Fikih - Muhammad Abu Rivai (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2023)
Crowdfunding services are institutions that can facilitate meetings between investors and small and medium enterprises (SMEs) who need funds through the company's digital platform. Investors who will invest through crowdfunding services can be converted into share ownership, debt ownership (bonds) or joint ownership (sukuk). Investors will get returns in the form of dividends or profit sharing from the company's profits which are distributed periodically. Meanwhile, SMEs get additional capital that is fast, easy and inexpensive to increase their business capacity. In doing business, of course everyone wants to get the maximum profit and minimize the risk of loss as small as possible. Risk itself is an inseparable part of life, because all activities must contain risks. One thing that can be done to minimize the risk of loss is to create a risk management strategy. Risk management is very important because it can maintain the continuity of the issuance of small and medium enterprise (MSMEs) sukuk by crowdfunding institutions. However, it is necessary to conduct a study to examine this in the perspective of fiqh rules The research method used in this study is a literature study. The tool to analyze it is the rule of fiqh (al kharja bidh dhaman) which means that profit is a reward for readiness to bear losses. In a mudharabah contract, profits and losses are shared. If the business is profitable, the investors and business actors will also benefit. If the business has incurred a loss, the investor and the business actor must both bear the loss. It is a mistake if the investor asks for the capital to be returned as long as it is not due to the carelessness of the business actor. Whereas in the wakalah contract, the person who receives power over the object being authorized must be a trustworthy person. The person who is given this mandate is not subject to dhaman (compensation) unless there is negligence. One way to measure unlawful risk mitigation practices is to use the al kharaj bidh dhaman rule. The parties to the contract should each have their own kharaj (rights) and dhaman (obligations). The practice of risk mitigation becomes problematic when there are parties who are safe from the risk or do not want to bear the portion of the risk that should be their responsibility. Bearing in mind that ownership creates rights and obligations, the rules for dividing the risk of loss are in accordance with the portion of ownership of each party. The bigger the portion, of course the bigger the risk that must be borne.